Access and the Changing Mission of Research Libraries - Wätjen, Hans-Joachim (LIBER Quarterly: The Journal of the Association of European Research Libraries, 1999)
The session of this morning deals with the coming century. But I am not a prophet foreseeing the future. I agree with the economist Edgar Fiedler who said in his Law of Prediction, „Forecasting is very difficult, especially if it’s about the future.” And Mirjam Foot is on the right side too. In the afternoon she will talk about change as the only certainty. Or in other words: today we live in an age of uncertainty and it will increase in the future!